Microwave-assisted chemical synthesis of conducting polyindole: Study of electrical property using Schottky junction - Tiwari M.; Kumar A.; Umre H.S.; Prakash R. (My University, 2025)
A facile and rapid enhanced microwave-assisted route for one-pot synthesis has been developed to polymerize indole moiety using two different oxidizing agents for 60 s exposure at 30 ± 1C. As-synthesized conducting polyindoles, obtained by varying the synthesis process and oxidant, have been well characterized by various techniques. UV-vis, FT-IR, and NMR have been used for their structural analysis while gel permeation chromatography, thermogravimetric analysis, and conductivity measurement to evaluate their enhanced properties and to perform a comparative study. Morphological texture of polyindole synthesized via different techniques has studied by scanning electron microscopy analysis. PIn synthesized by KIO3 (microwave synthesis) exhibit interconnecting texture which may be due to high level of supersaturation of solution under the influence of microwave irradiation. Thereafter, electrical property of spin-coated thin film of polyindole is examined using four probe method and Al metal/semiconducting material Schottky junction. Microwave-assisted polymer shows better performance for Schottky devices due to difference in charge transport, morphological texture, and distribution of Mn. The PIn synthesized via microwave irradiation with better charge transport across the metal/polymer interfaces shows the potential of this technique for synthesis of such polymers with enhanced electronic properties. © 2015 Wiley Periodicals, Inc.